FUNGSI HUKUM SEBAGAI PENGENDALIAN SOSIAL DARI PERSPEKTIF SOSIOLOGI HUKUM - Mohd. Yusuf D.M.; Ermanto; Cecep Sujapar (The Juris, 2022)
Society or social life is actually a collection of various kinds of relationships between its members. This relationship ultimately forms social life. Thus it can be said, that social life is the fabric of the various relationships that are carried out between members of society with one another. Everyone in association in society must pay attention to and implement (obey) legal regulations, in order to create an orderly and peaceful life. If there is a violation of the law against the applicable legal regulations, the violated regulations must be upheld, implementing the rule of law in a country is very difficult to separate from the political aspects of the country. It is the political situation that gives the style and form of implementing law enforcement. The formulation of the problem in this research is the function of law as social control from the perspective of legal sociology. The method used in this research is normative law. Based on the research results, it is known that the function of law as social control from the perspective of legal sociology is that in order for the function of law to work properly, there needs to be socialization of the law and it must be enforced fairly because this causes people to often take the law into their own hands in resolving the cases they face.